Realistic Dependence T-vc for Recent Cutting Materials - Vasilko, Karol; Duplak, Jan (Manufacturing Technology Journal, 2013)
Cutting property of tool materials is classically considered on the base of durability tests, the result of which is dependence of tool durability on cutting speed known as T-vc dependence. It was first developed by Taylor in 1906 to evalueate the durability of high-speed steel [1]. This relation, which is interpoled by a line in double logarithmic coordinate system, has been used also for the observation of the durability of sintered carbids and cutting tools made of ceramics. As the experiments show, T-vc dependence for such cutting materials is considerably different from the dependence for hig-speed steel. However, they have not been examined thoroughly yet because they require complex experimental tests. In the strive to make the tests simpler, ISO 3685 standard was formed: Tool-life testing with single-point turning tools [2], which, however, prescribes to evaluate durability only in limited range of cutting speeds. The aim of this paper is a suggestion of the evalueation of tool durability by the dependence of the size of tool wear on cutting speed (VB = f(vc) for constant machining time ( τ s ). The dependence has the same predication value as T-vc dependence and considerably shorter time is necessary for its formation [3].
Keywords: machining; cutting speed; tool durability